PEMBUATAN PIN 49JPH CAPACITY UP MENGGUNAKAN MESIN BUBUT TA SHING CROWN-4 - Wahidin, Dendi; Koswara, Engkos (Universitas Majalengka, 2025)
This research discusses the manufacturing process of the 49JPH Capacity Up Pin using the Ta Shing Crown-4 lathe machine at PT. Tri Jaya Teknik Karawang. The material used is S45C steel, which has mechanical properties that support strength and wear resistance. The pin production process includes planning, material and tool selection, and several turning steps: facing, straight turning, chamfering, thread cutting M24x3, taper turning, and fillet finishing. Machining parameters were calculated to determine spindle speed, cutting speed, depth of cut, and feed rate. Quality inspection was carried out using a vernier caliper and screw pitch gauge with a tolerance of 0.01 mm. The results show that the manufacturing process successfully produced pins according to design, with product quality meeting standards without surface defects. This indicates that the combination of Ta Shing Crown-4 lathe, S45C steel, and carbide cutting tools is effective in producing precise and durable pins for industrial applications.